Chidamide Inhibits Acute Myeloid Leukemia Cell Proliferation by lncRNA VPS9D1-AS1 Downregulation via MEK/ERK Signaling Pathway - Lin, Liman; Que, Yimei; Lu, Pingfan; Li, Huimin; Xiao, Min; Zhu, Xiaojian; Li, Dengju (Frontiers in Pharmacology, 2020)
Irregular histone modification and aberrant lncRNAs expression are closely related to the occurrence of tumors including acute myeloid leukemia (AML). However, the effects and specific underlying molecular mechanism of histone deacetylase inhibitors (HDACis) on lncRNA expression in AML cells are unclear. Here, we reported the effects of a novel HDACi Chidamide on proliferation and lncRNA expression in AML cells. Chidamide inhibited cell proliferation, blocked G1/S phase transition, and induced cell apoptosis through the caspase-dependent apoptotic pathway in AML cells. Chidamide also inhibited the formation of subcutaneous tumors. Transcriptome sequencing results showed that 1195 lncRNAs were co-upregulated and 780 lncRNAs were co-downregulated after Chidamide treatment of SKM-1 cells and THP-1 cells. Combined with transcriptome sequencing data and the GEPIA dataset, we found that VPS9D1-AS1 expression was negatively correlated with the survival of AML patients. VPS9D1-AS1 knockdown inhibited cell proliferation, arrested cell cycle, as well as inhibited the formation of subcutaneous tumors in vivo. VPS9D1-AS1 overexpression had the reverse effect. Furthermore, VPS9D1-AS1 knockdown inhibited the MEK/ERK signaling pathway, and thus enhanced the inhibitory effect of Chidamide on AML cell proliferation. These findings suggested that targeted regulation of VPS9D1-AS1 might overcome the limitations of Chidamide in the treatment of AML.